Pengaruh Subtitusi Tepung Sorgum (Sorghum bicolor L. Moench) dan Penambahan Tepung Daun Katuk (Sauropus androgynus (L.) Merr) terhadap Tingkat Kesukaan, Mutu Organoleptik dan Kandungan Gizi Mie Basah sebagai Altenatif Makanan untuk Ibu Menyusui - Irdati Ainina Fataya; Veni Indrawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast milk (ASI) is the primary and best food for infants because it contains almost all the nutrients in the right composition to meet the needs of the baby for optimal growth and development. Breastfeeding mothers require additional nutrients such as carbohydrates, protein, and iron. One of the food ingredients that contains carbohydrates, protein, and iron is sorghum and katuk leaves. Sorghum is rich in carbohydrates and protein, while katuk leaves contain lactagogue, which helps increase breast milk production. This study aims to analyze the effect of sorghum flour substitution and the addition of katuk leaves in wet noodles on the level of preference, organoleptic quality, and nutritional content of wet noodles as an alternative food for breastfeeding mothers. This study used a true experimental method with a 3x2 factorial design, involving three levels of sorghum flour substitution (10%, 20%, 30%) and two levels of katuk leaf flour addition (2%, 4%). A preference test was conducted with 35 panelists, while an organoleptic quality test was conducted with 25 panelists using a hedonic scale, analyzed with Friedman, Wilcoxon, and Two-Way Anova tests. The results showed that sorghum flour and katuk leaf flour substitutions significantly affected preference levels in terms of color, aroma, texture, and taste, with formula X1Y1 being the most preferred. Sorghum flour and katuk leaf flour substitution affected the organoleptic quality parameters of color and texture but did not influence aroma and taste. The best nutritional content of noodles from the preference test in formula X1Y1 (10% sorghum, 2% katuk leaves) per 100 grams was 6.08% protein, 42.51% carbohydrates, and 3.11% iron.